2015
DOI: 10.1111/jcmm.12541
|View full text |Cite
|
Sign up to set email alerts
|

Changes in short‐chain acyl‐coA dehydrogenase during rat cardiac development and stress

Abstract: This study was designed to investigate the expression of short-chain acyl-CoA dehydrogenase (SCAD), a key enzyme of fatty acid β-oxidation, during rat heart development and the difference of SCAD between pathological and physiological cardiac hypertrophy. The expression of SCAD was lowest in the foetal and neonatal heart, which had time-dependent increase during normal heart development. In contrast, a significant decrease in SCAD expression was observed in different ages of spontaneously hypertensive rats (SH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 23 publications
(27 reference statements)
3
20
0
Order By: Relevance
“…It had been reported that SCAD deficiency could be observed in pathological cardiomyocytes, but not in physiological cardiomyocytes (29). Additionally, this deficiency was closely related to the deactivation of peroxisome proliferator-activated receptor α (PPARα) (29). Up to now, we still could not find any hint to link the above-mentioned changes with ICH (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…It had been reported that SCAD deficiency could be observed in pathological cardiomyocytes, but not in physiological cardiomyocytes (29). Additionally, this deficiency was closely related to the deactivation of peroxisome proliferator-activated receptor α (PPARα) (29). Up to now, we still could not find any hint to link the above-mentioned changes with ICH (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…siRNA‐1186, the most efficient small interference RNA (siRNA) for SCAD, was used for our experiments . The sequence of siRNA‐1186 were: sense 5′‐CCGCAUCACUGAGAUCAUTT‐3′ and antisense 5′‐AUAGAUCUCAGUGAU GCGGTT‐3′.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous researches had revealed that SCAD expression was significantly down‐regulated in pathological cardiac hypertrophy in vivo and in vitro for the first time. Moreover, we also have found that pathological cardiac hypertrophy exhibited SCAD changes in myocardial fatty acids utilization . Nevertheless, the role of SCAD in cardiomyocyte apoptosis is currently still unknown.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations